OBA in Senegal : Designing Technology-Neutral Concessions for Rural Electrification - de Gouvello, Christophe; Kumar, Geeta (World Bank, Washington, DC, 2012)
The government of Senegal has made rural electrification a priority, recognizing its importance in reducing poverty and redressing development imbalances. A new program that combines output-based aid (OBA) subsidies with technology neutral competitive bidding is seen as more promising. This program has the potential to align private incentives with public sector objectives of maximizing the number of rural households served under a sustainable commercial scheme. This newsletter touches on the these OBA subsidies and discusses how to bridge the rural-urban energy divide via public-private partnerships, the new rural electrification strategy, the new tariff schedule, the OBA subsidy design, the bidding process, and funding sources. The newsletter also gives an update on current results and what the next recommended steps are.